AN INVESTIGATION INTO ADVERTISING SLOGANS IN ENGLISH AND VIETNAMESE - Ph.D. Lê Tấn Thi (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The study is implemented with the aims of finding the similarities and differences of English and Vietnamese advertising slogans in terms of lexical, syntactic and stylistic features. Besides, this study is believed to partly contribute in order to help Vietnamese learners get better understandings of the linguistic features of advertising slogans. To some extent, the research will enable them to write a successful advertising slogan, manifesting completely the culture of their business.